2 - ‘Blood Money’, Migrants’ Enslavement and Insecurity in Africa’s Sahel and Libya - Kam Kah, Henry (Africa Development, 2019)
This article examines how and why the pursuit of greener pastures in Europe and Libya has resulted in the enslavement of migrants from sub-Saharan Africa by human smugglers, felonious gangs, disaffected groups and government officials in an uncertain and unhealthy desert setting in Niger and Libya. Many young men, women and children are easily traded, sexually abused, made to work for long hours without pay, abandoned in the wild and/or tortured to death. The messy governance system in several migrants’ countries of origin and transit countries like Somalia, Eritrea, Nigeria, Côte d’Ivoire, Democratic Republic of the Congo, Mali, Niger, Burkina Faso and Sudan has fuelled migration, enslavement and insecurity. Those who have endured this brutish treatment recount frightful stories of the horrors of migration across the Sahel. Numerous calls for efforts to mitigate mass migration and human enslavement in the twenty-first century have apparently fallen on deaf ears. This phenomenon in Niger and Libya was investigated through a content analysis of victims’ accounts and reports by humanitarian organisations and journalists. In fact, modern migrants’ enslavement for cash through open purchase, sale and use for sexual pleasures have resulted in and still lead to many deaths today. Many African migrants who anticipate a better life in Libya or Europe have been trapped and persecuted by soulless individuals who want to make quick money through dehumanising, sexually abusing and killing them. Stable and sustainable governance is indispensable if we really want to address this problem and reinstate human self-possession in Africa’s Sahara Desert.